2017
DOI: 10.1016/j.athoracsur.2017.06.051
|View full text |Cite
|
Sign up to set email alerts
|

Timeliness of Care and Lung Cancer Tumor-Stage Progression: How Long Can We Wait?

Abstract: Background Timely care of lung cancer is presumed critical, yet clear evidence of stage progression with delays in care is lacking. We investigated the reasons for delays in treatment and the impact these delays have on tumor-stage progression. Methods We queried our retrospective database of 265 veterans who underwent cancer resection from 2005 to 2015. We extracted time intervals between nodule identification, diagnosis, and surgical resection; changes in nodule radiographic size over time; final pathologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(41 citation statements)
references
References 41 publications
2
36
0
1
Order By: Relevance
“…Clinical stage was not available in this study to assess the proportions of patients upstaged at the time of surgery. Similarly, Maiga and coworkers [24] analyzed 197 lung cancer patients who had a tissue diagnosis and subsequently underwent surgical resection (median diagnosis to surgery time 53 days) at the VA Tennessee Valley Healthcare System from 2005 to 2015, and in univariable analyses, found no significant correlation between time to resection with tumor progression, defined as tumor growth > 0 mm between radiographic and pathologic tumor size; this definition is unlikely to be sensitive to small/subtle changes in tumor growth. In our subgroup analysis of stage I patients, 52 (43%) underwent surgical resection, 18 of whom (35%) were upstaged at the time of surgery; there was no difference in TTT in those upstaged versus those not upstaged (mean 42 vs. 33 days, respectively, t -test for equality of means p = 0.25).…”
Section: Discussionmentioning
confidence: 84%
“…Clinical stage was not available in this study to assess the proportions of patients upstaged at the time of surgery. Similarly, Maiga and coworkers [24] analyzed 197 lung cancer patients who had a tissue diagnosis and subsequently underwent surgical resection (median diagnosis to surgery time 53 days) at the VA Tennessee Valley Healthcare System from 2005 to 2015, and in univariable analyses, found no significant correlation between time to resection with tumor progression, defined as tumor growth > 0 mm between radiographic and pathologic tumor size; this definition is unlikely to be sensitive to small/subtle changes in tumor growth. In our subgroup analysis of stage I patients, 52 (43%) underwent surgical resection, 18 of whom (35%) were upstaged at the time of surgery; there was no difference in TTT in those upstaged versus those not upstaged (mean 42 vs. 33 days, respectively, t -test for equality of means p = 0.25).…”
Section: Discussionmentioning
confidence: 84%
“…We therefore have provided evidence tables with the new studies identified, with additional methodology comments (e-Appendix 2, 3). [6][7][8][9][10][11][12][13][14][15][16][17][18][57][58][59][60][61] The available evidence is often conflicting regarding the relationship between timeliness of care and outcome. 7,13,17 Paradoxically, multiple studies reported that more timely care was associated with worse outcomes.…”
Section: Remarksmentioning
confidence: 99%
“…NSCLC grows rapidly, and a delay in initiation of treatment can result in disease progression and death 24‐26 . A single‐center study showed no significant correlation between tumor growth and time to resection 27 . However, in that study, there was no multivariate adjustment for clinical or biological factors that underlies growth risk 27 .…”
Section: Discussionmentioning
confidence: 88%